Obstacles and expectations of rare disease patients and their families in Türkiye: ISTisNA project survey results - Hatirnaz Ng, Ozden; Sahin, Ilayda; Erbilgin, Yucel; Ozdemir, Ozkan; Yucesan, Emrah; Erturk, Nazli; Yemenici, Merve; Akgun Dogan, Ozlem; Ugur Iseri, Sibel Aylin; Satman, Ilhan; Alanay, Yasemin; Ozbek, Ugur (Frontiers in Public Health, 2023)
Rare disease patients constitute a significant part of the healthcare system of all countries. However, the information on the experiences during disease processes and daily life of rare disease patients is still limited. So far, there is a small number of studies conducted in Türkiye, and they mainly cover specific issues like education or anxiety. Here we present a comprehensive survey analysis conducted among the patients and their families within the scope of the Istanbul Solution Platform for Undiagnosed and Rare Diseases-ISTisNA project. A total of 498 individuals responded to the survey, and 58% of the participants answered all questions. The majority of the patients were in the age range of 1–10 years (44.7%), and 91% of all the patients had a precise diagnosis. The diagnosis rate in the first 6 months was 69%, and almost 10% of the patients remained undiagnosed. The mothers were the primary caregivers (72%). Nearly 30% of the caregivers had to quit their jobs and 25% of the patients (0–18 years) had to leave school. Accessing physicians with relevant specialization and reaching treatments/medications/supplements were the two main obstacles the participants mentioned, with a frequency of 81% and 73%, respectively. Around 50% of participants noted that they commonly faced difficulties at work/school and in their social lives. The highest expectation or priority was the establishment of rare disease-specific diagnosis and treatment centers, accurate and detailed information on diseases in the Turkish language, and easy access to physicians, treatments, and supportive therapies. To the best of our knowledge, this is the most comprehensive survey conducted on the rare disease community in Türkiye. These results show that regardless of the country, the individuals affected by rare diseases and their families have similar problems and expectations. On the other hand, regional and country-specific issues are still in the line to be solved. These studies can provide a deeper insight into rare diseases and guide the activities of Türkiye's national rare disease action plan.